2010
DOI: 10.1371/journal.pone.0010786
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to PI3K and MEK Inhibitors in Breast Cancer. Use of a 3D Culture System to Study Pathways Related to Hormone Independence in Mice

Abstract: BackgroundA significant proportion of breast cancer patients face failure of endocrine therapy due to the acquisition of endocrine resistance. We have explored mechanisms involved in such disease progression by using a mouse breast cancer model that is induced by medroxyprogesterone acetate (MPA). These tumors transit through different stages of hormone sensitivity. However, when cells from tumor variants were seeded on plastic, all were stimulated by progestins and inhibited by antiprogestins such as RU486. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 58 publications
4
14
0
Order By: Relevance
“…The fact that chemical inhibitors of PI3K block the mitogenic signaling in breast cancer cells has been reported earlier [9,23]. This is also illustrated by the effect of LY 294002 on the expression of cyclin A (Figure 4, upper panel).…”
Section: Resultssupporting
confidence: 77%
“…The fact that chemical inhibitors of PI3K block the mitogenic signaling in breast cancer cells has been reported earlier [9,23]. This is also illustrated by the effect of LY 294002 on the expression of cyclin A (Figure 4, upper panel).…”
Section: Resultssupporting
confidence: 77%
“…5). PTEN is a negative regulator of Akt activity, and the higher expression of this gene in C4-HD tumors is in agreement with recent work by our group showing that C4-HI tumors exhibit elevated activation of Akt compared with that in C4-HD tumors [36]. To study the expression of MMP9 and MMP13 proteins, we used IF experiments.…”
Section: Validation Of Selected Differentially Expressed Genessupporting
confidence: 86%
“…For example, cell proliferation inhibitor Emodin is justly proved to function in a MAPK way, targeting at ERα (Jia-Qi et al, 2014). But endocrine therapy targeting at ER or HER don't receive much effect as imaged, now, researches have showed that the ERK is closely connected to hormone resistance by the oncogenic RAS-MEK-ERK pathway (Polo et al, 2010). So, specific inhibitors of ERK kinase (MEK) should be of help.…”
Section: Mapk and Breast Cancermentioning
confidence: 99%